Protecting franchise chains against weather risk: A design science approach - Bertrand, Jean-Louis; Brusset, Xavier; Chabot, Miia (Journal of business research, 2021)
Franchisees are often small business owners whose sales, profitability, and financial equilibrium in the first years of operation are increasingly being impacted by weather variability. The literature has analysed the effectiveness of various guarantees offered by franchisors in franchise agreements, but the case of hedging the local weather risk to which each franchisee is exposed has never been addressed. Using Design Science, we show that franchisors operating in one of the activities which are among the 70% of activity sectors exposed to weather risks, can support the setup of franchises, measure their weather risk and incorporate financial protections against the consequences of adverse weather in the franchise agreement. By doing this they can reduce the risk of financial distress, provide an innovative service, and reinforce the quality of the relationship with their franchisees.